Clinical performance of an infliximab rapid quantification assay - Magro, F. (2017)
BACKGROUND: Therapeutic drug monitoring (TDM)-based algorithms can be used to guide infliximab (IFX) adjustments in inflammatory bowel disease (IBD) patients. This study aimed to explore a rapid IFX-quantification test from a clinical perspective. METHODS: This manuscript describes a prospective cohort study involving 110 ulcerative colitis (UC) patients on the maintenance phase of IFX. IFX trough levels were quantified using a rapid quantification assay and a commonly-used reference kit. RESULTS: Irrespective of the assay used to measure IFX, its through levels were statistically different between patients with and without endoscopic remission (Mayo endoscopic score = 0), as well as between patients stratified by their faecal calprotectin (FC) levels. Despite the fact that the two methods correlated well with each other [Spearman's rank correlation coefficient = 0.843, p < 0.001; intraclass correlation coefficients = 0.857, 95% confidence interval (CI): 0.791-0.903], there was a discernible systematic variation; values obtained with the reference kit were on average 2.62 units higher than those obtained with the rapid assay. Notwithstanding, 3 µg/ml was shown to be an acceptable cut-off to assess endoscopic status and inflammatory burden levels using both assays. The percentage of patients that had a positive outcome when the IFX concentration measured by the rapid assay ranked above 3 µg/ml was 88% both for a Mayo endoscopic score ⩽ 1 and for an FC concentration <250 µg/g. CONCLUSIONS: Based on this study, we concluded that using the rapid IFX assessment system with a 3 µg/ml threshold is a reliable alternative to the time-consuming enzyme-linked immunosorbent assays in patients on the maintenance phase of IFX.